SOX2, OCT4 and NANOG: The core embryonic stem cell pluripotency regulators in oral carcinogenesis - Swain, Niharika (J Oral Maxillofac Pathol, 2020)
Embryonic stem cells provide their major contribution to embryogenesis through formation of germ layers as they have pluripotency potential and capacity for self-renewal. Retention of pluripotency of these stem cells depends on expression/level of transcription factors, i.e., SOX2, OCT4 and NANOG. During organogenesis, the altered expression of the molecules also influences these stem cells to lose their pluripotency and turn toward the lineage selection. As the differentiation progresses, the maintenance of the somatic cells including the oral squamous cells also depends on differential expression of the transcription factors to some extent. Recently, many experimental and observational studies documented the significant contribution in carcinogenesis of various human cancers. In this review, we have attempted to summarize the evidences indicating about the putative role of these master pluripotency regulators in various phases of oral carcinogenesis i.e. initiation , progression and prognosis of oral squamous cell carcinoma.